KAJIAN LITERATUR PEMANFAATAN ADSORBEN KITOSAN TERMODIFIKASI ARANG AKTIF LIMBAH ORGANIK TERHADAP LOGAM BERAT - Arsyakia, Tarisa; Koesnarpadi, Soerja; Lianasari, Ika Yekti (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
A literature review on the utilization of chitosan adsorbent modified organic waste activated charcoal against heavy metals has been conducted. From the results of the study, it was obtained that organic waste activated charcoal still has chemical content in the form of cellulose, lignin, hemicellulose, carboxymethyl cellulose ranging from 33.61-65,7%. The carbon compounds formed ranged from 66.60-86.4%. The organic waste activated charcoal used includes coffee grounds; tea grounds; teak wood powder; coconut shell; durian peel waste; pineapple peel waste; salak fruit seed waste; and rubber fruit shell. Activated charcoal is modified with chitosan to optimize pores, expand the surface, and increase adsorption power. The modification process is by mixing chitosan with a certain weight and dissolving it in 1-3% CH3COOH, then adding activated charcoal with a certain weight, stirring until a homogeneous gel is formed. Next, it was baked at 60ºC for 24 hours. The results formed were mixed into NaOH with a certain concentration, then washed with distilled water until neutral and stored in a desiccator. The chitosan - activated charcoal adsorbent was then contacted with heavy metals Arsenic (As); Lead (Pb); Cadmium (Cd); Copper (Cu); Zinc (Zn); and Iron (Fe). The results obtained percent absorption and adsorption capacity ranged from 85.32-99.992% and 0.1236-177.7035 mg/g. The values of percent absorption and adsorption capacity are influenced by the surface area, concentration, and adsorbent that needs to be activated. Keywords : Activated Charcoal, Chitosan, Modification, Heavy Metal